World Economic Outlook, April 2015 : Uneven Growth: Short- and Long-Term Factors. (World Economic Outlook; World Economic Outlook ;, 2015)
Global growth remains moderate and uneven, and a number of complex forces are shaping the outlook. These include medium- and long-term trends, global shocks, and many country- or region-specific factors. The April 2015 WEO examines the causes and implications of recent trends, including lower oil prices, which are providing a boost to growth globally and in many oil-importing countries but are weighing on activity in oil-exporting countries, and substantial changes in exchange rates for major currencies, reflecting variations in country growth rates and in exchange rate policies and the lower price of oil. Additionally, analytical chapters explore the growth rate of potential output across advanced and emerging market economies, assessing its recent track and likely future course; and the performance of private fixed investment in advanced economies, which has featured prominently in the public policy debate in recent years, focusing on the role of overall economic weakness in accounting for this performance.